2005
DOI: 10.4028/www.scientific.net/msf.475-479.559
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization in AZ31 Magnesium Alloy during Hot Deformation

Abstract: In this study, isothermal torsion tests were carried out on magnesium AZ31B alloy under constant strain rate conditions, in the range of 250 to 400oC at 0.01, 0.1, and 1.0 s-1. Alloy flow stress dependence on strain rate and temperature can be described by a power law with activation energy of 130 kJ/mol. Microstructural examination of hot deformed samples shows very fine recrystallized grains decorating grain boundaries of larger gains in the form of a necklace. These fine grains are produced by dynamic recry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The distributions are not random and exhibit three distinct maxima. The first maxima stands out near low misorientation and has been assigned in the literature to induced subgrain boundaries [17]. The last maxima can be attributed to deformation introduced during the sample preparation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The distributions are not random and exhibit three distinct maxima. The first maxima stands out near low misorientation and has been assigned in the literature to induced subgrain boundaries [17]. The last maxima can be attributed to deformation introduced during the sample preparation.…”
Section: Discussionmentioning
confidence: 97%
“…It is evident in this sample that dynamic recrystallization is partial, i.e. the fraction of recrystallized grains remains very small with no significant grain refinement [16,17]. From Figures 3a to 3d, we can depict that an increase of the reduction ratio led to an increase of the overall recrystallized area.…”
Section: Deformation Microstructure and Texturementioning
confidence: 95%
“…Provided that negligible grain growth occurs during the cooling period, it could be expected that the average grain sizes found in the stir zones of AZ31 spot welds were mainly determined by the high temperature deformation conditions imposed by the rotating tool. In this connection, a previous work by Essadiqi et al 27 confirmed that the recrystallisation process in AZ31 alloy is complete when the deformation temperature exceeds 250uC and the strain rate exceeds 1 s 21 and that the final grain size will increase with increasing temperature.…”
Section: Discussionmentioning
confidence: 61%
“…The superplastic behaviour is attributed to the bimodal grain structures where the large grains contribute to the strain hardening of the alloy and the small grains provide high strain rate sensitivity due to diffusion controlled process. Torsion studies performed on the alloy by Spigarelli et al 30 and Essadiqi et al 18 suggest DRX behaviour and necklace formation followed by reduction in grain size at temperatures 250-400uC and strain rates up to 1 s 21 . Spigarelli et al evaluated the value of activation energy of deformation as 155 kJ mol 21 based on torsion tests.…”
Section: Hot Deformation Of Az31 Alloymentioning
confidence: 97%
“…8 If the basal plane is perpendicular or almost parallel to the loading axis, the shear stress falls to very low value and a large force is needed to initiate slip. At high temperatures (.225uC), the pyramidal planes 10-11 È É get active as slip planes with [11][12][13][14][15][16][17][18][19][20] Â Ã as the direction of slip. The 10 -11 È É are the second most closely packed structures after the basal plane.…”
Section: Deformation Mechanism In Hcp Metals and Mgmentioning
confidence: 99%